2017
DOI: 10.12669/pjms.332.11569
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility in commonly isolated pathogens from urinary tract infection in a cohort of subjects from low socioeconomic strata.

Abstract: Background and Objective:Urinary tract infection is one of the commonest infections seen in clinical practice. Lack of compliance and unjustified antibiotic prescriptions has resulted in bacterial resistance and is proving as a major challenge in the management of these infections. Our aim was to identify the sensitivity pattern of commonly used antibiotics against urinary tract infections so as to suggest an improvised line of action against bacteria causing urinary tract infections’.Method:This was a hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
4
14
0
Order By: Relevance
“…E. coli susceptibility to fluoroquinolones in the current study ranged from 60.3% (norfloxacin) to 70.4% (ciprofloxacin) which was similar to the rates observed in Brazil and Korea (Reis et al 2016;Park et al 2017). Another study reported that E. coli was least sensitive to cephalosporins (7.0-34.0%) and fluoroquinolones (26.0-28.0%); however, a study was conducted on a population from low socioeconomic strata (Kidwai et al 2017). A good empirical choice seems to be nitrofurantoin but a study carried out in Poland showed a high proportion of resistance to nitrofurantoin among E. coli isolates (Stefaniuk et al 2016).…”
Section: Discussionsupporting
confidence: 82%
“…E. coli susceptibility to fluoroquinolones in the current study ranged from 60.3% (norfloxacin) to 70.4% (ciprofloxacin) which was similar to the rates observed in Brazil and Korea (Reis et al 2016;Park et al 2017). Another study reported that E. coli was least sensitive to cephalosporins (7.0-34.0%) and fluoroquinolones (26.0-28.0%); however, a study was conducted on a population from low socioeconomic strata (Kidwai et al 2017). A good empirical choice seems to be nitrofurantoin but a study carried out in Poland showed a high proportion of resistance to nitrofurantoin among E. coli isolates (Stefaniuk et al 2016).…”
Section: Discussionsupporting
confidence: 82%
“…It was also highlighted recently that emergence of MDR bacteria are on raise and 77.5% of all the screened isolates were resistant to three or more than three of the tested antibiotics [23]. A report from Sindh province of Pakistan showed that nearly half of the isolates from UTI have shown resistance to most of the commonly used antibiotics recommended in the guidelines especially the floxacin group probably because of its unwarranted use [24]. A large scale retrospective study from Karachi analyzed the data of 27,852 blood cultures over the period of four years (2010, 2012, 2014 and 2015) and the results showed that Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Multi drug resistance (MDR) is increasing in Pakistan and it has been highlighted in a study that 77.5% of all the screened isolates were resistant to three or more than three of the tested antibiotics [10]. Different reports regarding the development of antibiotic resistance in Pakistan confirm the drastic increase of antibiotic resistance or even the development of MDR across the country [11][12][13][14][15][16][17][18].…”
Section: Letter To the Editor Dear Editormentioning
confidence: 99%